The intention to share and re-shared among the young adults towards a posting at social networking sites - Teh, Phoey Lee *; Lim, Paul Huah *; Si, Yain-Whar (Springer International Publishing, 2014)
The activity of sharing information among the young adults over the Internet has led to various types of damages in the community. This study explores the damages leading from posting of young adults’ overs the social network. The damages in this context refer to the damages in the form of business reputation, psychologist damages, cyber bullying and etc. In order to provide a neutralizing platform to these damages, the intention on the sharing and re-sharing between the postings among the young adults is studied. This paper summarizes the result of the intention to share and re-shared mechanism of the young adults on a posting at social networking sites.